Regulation of Thermogenic Adipocyte Differentiation and Adaptive Thermogenesis Through Histone Acetylation - Ong, Belinda X.; Brunmeir, Reinhard; Zhang, Qiongyi; Peng, Xu; Idris, Muhammad; Liu, Chungang; Xu, Feng (Frontiers in Endocrinology, 2020)
Over the past decade, the increasing prevalence of obesity and its associated metabolic disorders constitutes one of the most concerning healthcare issues for countries worldwide. In an effort to curb the increased mortality and morbidity derived from the obesity epidemic, various therapeutic strategies have been developed by researchers. In the recent years, advances in the field of adipocyte biology have revealed that the thermogenic adipose tissue holds great potential in ameliorating metabolic disorders. Additionally, epigenetic research has shed light on the effects of histone acetylation on adipogenesis and thermogenesis, thereby establishing the essential roles which histone acetyltransferases (HATs) and histone deacetylases (HDACs) play in metabolism and systemic energy homeostasis. In regard to the therapeutic potential of thermogenic adipocytes for the treatment of metabolic diseases, herein, we describe the current state of knowledge of the regulation of thermogenic adipocyte differentiation and adaptive thermogenesis through histone acetylation. Furthermore, we highlight how different HATs and HDACs maintain the epigenetic transcriptional network to mediate the pathogenesis of various metabolic comorbidities. Finally, we provide insights into recent advances of the potential therapeutic applications and development of HAT and HDAC inhibitors to alleviate these pathological conditions.